Fertility Sparing Treatment in Patients With Early Stage Endometrial Cancer, Using a Combination of Surgery and GnRH Agonist: A Monocentric Retrospective Study and Review of the Literature - Tock, Stéphanie; Jadoul, Pascale; Squifflet, Jean-Luc; Marbaix, Etienne; Baurain, Jean-François; Luyckx, Mathieu (Frontiers in Medicine, 2018)
Objectives: To evaluate the efficacy and safety of gonadotropin-releasing hormone (GnRH) agonist after endometrial resection in women suffering early stage endometrial carcinoma (EC) and/or endometrial intra-epithelial neoplasia (EIN). Design: A retrospective review of clinical files between January 1999 and December 2016. Setting: University hospital. Patients: 18 women younger than 41 years with grade 1 endometrial carcinoma (G1EC) and/or Endometrial intra-epithelial neoplasia (EIN). Interventions: All patients received GnRH agonist for 3 months after an endometrial resection combined with a laparoscopy to exclude concomitant ovarian tumour and/or other extra-uterine disease. The patient underwent a follow-up of 3 months interval with endometrial sampling by hysteroscopy. Main Outcome Measure(s): The recurrence rate and the pregnancy rate after fertility sparing treatment. Results: We identified 9 patients with EIN (50%), 7 patients with G1EC (38.9%), 1 with combined histology (5.5%) and 1 with G2EC (5.5%). After a median follow-up of 40,7 months, 12 patients conserved their uterus (66.7%), and 8 (53,3%) patients were pregnant with a total of 14 pregnancies among those who tried to become pregnant. We observed a complete response rate in 12 patients (66.7%) but 3 of these patients relapsed (25%). We also found a stable disease in 6 patients (33.3%). Conclusions: Compared with other fertility sparing treatments, GnRH agonist after surgery is an effective fertility-sparing strategy for women with EIN and/or G1EC. We recommend hysterectomy once a family has been completed even if the literature does not clearly lead to radical surgery.